2017
DOI: 10.1371/journal.pone.0184920
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section without medical indication and risk of childhood asthma, and attenuation by breastfeeding

Abstract: BackgroundPrevious studies suggest that caesarean section (CS) may increase the risk of asthma in children, but none of them could preclude potential confounding effects of underlying medical indications for CS. We aim to assess the association between CS itself (without medical indications) and risk of childhood asthma.MethodsWe conducted a hospital-based case-control study on childhood asthma with 573 cases and 812 controls in Shanghai. Unconditional logistic regression models in SAS were employed to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 19 publications
0
32
1
3
Order By: Relevance
“…None of the women fulfilled the criteria for severe respiratory insufficiency, which would be a contraindication to vaginal delivery. Vaginal delivery is important for women with bronchial asthma because neonates delivered via elective cesarean have a 58.0% higher risk of subsequently developing bronchial asthma . Children of mothers with asthma have a primarily higher risk of atopy, not only because of genetics but also because of epigenetic modifications of immunoregulatory and proinflammatory pathways …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the women fulfilled the criteria for severe respiratory insufficiency, which would be a contraindication to vaginal delivery. Vaginal delivery is important for women with bronchial asthma because neonates delivered via elective cesarean have a 58.0% higher risk of subsequently developing bronchial asthma . Children of mothers with asthma have a primarily higher risk of atopy, not only because of genetics but also because of epigenetic modifications of immunoregulatory and proinflammatory pathways …”
Section: Discussionmentioning
confidence: 99%
“…12 In the present study, in cooperation with an orthopedic spe- asthma. 15 Children of mothers with asthma have a primarily higher risk of atopy, not only because of genetics but also because of epigenetic modifications of immunoregulatory and proinflammatory pathways. 16 A study based on a validated questionnaire found that severe fear of childbirth was reported by 11.3% of primiparas and 10.9% of multiparas, and these women have a 66.0% higher chance of delivering via elective cesarean.…”
Section: Discussionmentioning
confidence: 99%
“…; Chu et al . ). The longer term effects of CS on wheeze and allergy have been explored in a metanalysis; there was an increased odds ratio for asthma up to 12 years of age, with less conclusive results for wheeze and allergy/atopy (Keag et al .…”
Section: Introductionmentioning
confidence: 97%
“…Epidemiological studies have linked CSs with a higher risk of non-communicable diseases such as obesity [13,14] and allergy [15]. Indeed, the CS procedure is characterized by pre-and intra-partum antibiotic exposure and other medical practices, which may affect early gut colonization and predispose the infant to developing immune-related disorders later in life, including asthma [16][17][18], allergy [19][20][21], obesity [22,23] and diabetes [24,25]. Hospital interventions during birth are critical for pioneer microbial colonizers and proper immune system maturation [26,27], which may impact adult health [28,29].…”
Section: Introductionmentioning
confidence: 99%